A Test of the Bistrategic Control Hypothesis of Adolescent Popularity. Issue 3 (25th June 2019) - Hartl, Amy C.; Laursen, Brett; Cantin, Stéphane; Vitaro, Frank
Abstract : Resource Control Theory (Hawley, 1999) posits a group of bistrategic popular youth who attain status through coercive strategies while mitigating fallout via prosociality. This study identifies and distinguishes this bistrategic popular group from other popularity types, tracing the adjustment correlates of each. Adolescent participants (288 girls, 280 boys; M age = 12.50 years) completed peer nominations in the Fall and Spring of the seventh and eighth grades. Longitudinal latent profile analyses classified adolescents into groups based on physical and relational aggression, prosocial behavior, and popularity. Distinct bistrategic, aggressive, and prosocial popularity types emerged. Bistrategic popular adolescents had the highest popularity and above average aggression and prosocial behavior; they were viewed by peers as disruptive and angry but were otherwise well‐adjusted.